Pengaruh Pendampingan, Motivasi Dan Kepercayaan Anggota Terhadap Work Engagement Anggota Lembaga Psikologi Eksha Fit Cabang Jombang - Anta Salam, Muhammad Khairil; Abdillah, Adil; Kridaningsih, Anna (PRAGMATIS, 2023)
This study aims to examine the influence of mentoring, motivation, and trust on work engagement in members of the Jombang Branch of the Eksha Fit Psychology Institute. This research is included in quantitative research because the approach used for research proposals, processes, hypotheses, going to the field, data analysis, data conclusions to writing uses aspects of measurement, calculation, formula, and certainty of numerical data. The population in this study is 118 members of the Jombang branch of the Ekshafit Institute. The sampling technique uses the Accidental Sampling technique, the determination of the number of samples using the Slovin formula gets as many as 75 members. The results of the t-test stated that mentoring and motivation did not have a significant effect on work engagement, trust had a significant effect on work engagement. Based on a simultaneous test (Test F), the variables of mentoring, motivation, and trust have a joint effect on work engagement